The undervalued set piece: Analysis of soccer throw-ins during the English Premier League 2018-2019 season - Stone, J. A.; Smith, A.; Barry, A. (International Journal of Sports Science & Coaching, 2021)
Set pieces in soccer (i.e., free kicks and corners) have been examined in detail and are a common focus for coaches during training and performance preparation. However, limited evidence is available on the impact of throw-ins on soccer performance and if coaches should dedicate time in training towards this specific set piece. Therefore, this research aimed to firstly examine if throw-in performance is linked with soccer performance, and secondly the effect throw-in direction and length has on first contact success rate, possession retention, mean time in possession and shot creation. 16,154 throw-ins from 380 English Premier League matches during the 2018-2019 season were analysed. Higher final league position was correlated to increased throw-in first contact success and possession retention. 83% of throw-in`s resulted in a successful first contact, 54% resulted in possession being retained and 8.8% of throw-ins led to a shot at goal from the possession achieved after a successful first contact. Throw-in`s which went backwards or laterally in direction resulted in increased first contact success, retaining of possession, and shot creation. The least efficient throw-in was forwards and long, which resulted in both reduced first contact success and possession retention. Findings highlight, that throwing the ball laterally or backwards should be a focus for coaches and players during attacking training. In contrast, a team`s defensive strategy should reduce the opportunities to throw backwards or laterally with a higher press and look to force a long forward throw-in, therefore, increasing the likelihood of winning possession and counter attacking.